BIMBINGAN DAN PELATIHAN PENTINGNYA BERKOMUNIKASI DAN BERPENAMPILAN YANG BAIK DALAM MENGHADAPI JOB INTERVIEW BAGI SISWA SISWI SMK NATIONAL MEDIA CENTER KOTA MALANG - Farika Nikmah; Nilawati Fiernaningsih; Lilies Nur Ainie; Siti Nurbaya; Yosi Afandi (Publisher UPT P2M Politeknik Negeri Malang, 2017)
PKM target are students of SMK National Media Center, Malang which is between 15 until 18 years, where that age is still in the stage of finding identity, have an idolized figure and effort to follow what became a trend.With these psychological conditions, there are those who still need helpand guidance, so this activity is given material on how to communicate and good personalityfor post-work preparation.Activities undertaken by delivering the material about how to be a good communicator and good personality by lectures and discussions method, and frequently asked questions. Finally, a questionnaire is given to make a conclusion of the activity. Make sure that students understand of the material presented.